Implementasi dan Prinsip Akad Murabahah dan Musyarakah Mutanaqishah pada Produk Syariah pada Bank Muamalat Indonesia - Huda, Nurul; Maharani, Arinda (Journal of Sharia Economy and Islamic Tourism, 2023)
Abstract: Islamic banks as financial institutions whose operations are based on sharia principles, then in the product system offered using sharia contracts. Of the variety of contracts that can be applied in Islamic banks, there are contracts with cooperation patterns, in addition to the buying and selling and leasing/wage payment patterns which form the basis of commercial business. The contract for the cooperation pattern is mudharabah and musyarakah. This study aims to analyze the contract pattern of cooperation in Islamic banks in the perspective of Islamic economic law. The results of the discussion are operational products offered by Islamic banks with mudharabah patterns found in funding and financing products, while musyarakah is limited to financing. The implementation of mudharabah and musyarakah contracts in Sharia Banks in the study of sharia economic law is permissible and has legality on the basis of sharia principles, because mudharabah and musyarakah contracts are cooperative-patterned agreements in accordance with the guidance of sharia contracts in muamalah fiqh.Abstrak: Bank Syariah sebagai lembaga keuangan yang operasionalnya berdasarkan prinsip syariah, maka dalam sistem produk yang ditawarkan menggunakan akad-akad syariah. Dari beragamnya akad yang dapat diterapkan di bank syariah terdapat akad dengan pola kerja sama, selain pola jual-beli dan sewa-menyewa/upah mengupah yang menjadi landasan komersial bisnis. Akad pola kerja sama tersebut adalah mudharabah dan musyarakah. Penelitian ini bertujuan menganalisis akad pola kerja sama di bank syariah dalam perspektif hukum ekonomi syariah. Hasil pembahasan yakni operasional produk yang ditawarkan bank syariah dengan pola mudharabah terdapat pada produk pendanaan dan pembiayaan, sedangkan musyarakah terbatas pada pembiayaan. Implementasi akad mudharabah dan musyarakah di Bank Syariah dalam kajian hukum ekonomi syariah adalah boleh dilaksanakan dan memiliki legalitas atas dasar prisip syariah, sebab akad mudharabah dan musyarakah merupakan akad berpola kerja sama yang sesuai dengan tuntunan akad syariah dalam fikih muamalah.